Cytokine crowdsourcing: multicellular production of TH17-associated cytokines. Issue 3 (29th December 2014) - Busman-Sahay, Kathleen O; Walrath, Travis; Huber, Samuel; O'Connor, William
Abstract : Review of critical non-TH17 sources of IL-17A and associated cytokines during inflammation in mucosal tissues, with a focus on leukocytes of the gastrointestinal tract. Abstract: In the 2 decades since its discovery, IL-17A has become appreciated for mounting robust, protective responses against bacterial and fungal pathogens. When improperly regulated, however, IL-17A can play a profoundly pathogenic role in perpetuating inflammation and has been linked to a wide variety of debilitating diseases. IL-17A is often present in a composite milieu that includes cytokines produced by TH 17 cells (i.e., IL-17F, IL-21, IL-22, and IL-26) or associated with other T cell lineages (e.g., IFN- γ ). These combinatorial effects add mechanistic complexity and more importantly, contribute differentially to disease outcome. Whereas TH 17 cells are among the best-understood cell types that secrete IL-17A, they are frequently neither the earliest nor dominant producers. Indeed, non-TH 17 cell sources of IL-17A can dramatically alter the course and severity of inflammatory episodes. The dissection of the temporal regulation of TH 17-associated cytokines and the resulting net signaling outcomes will be critical toward understanding the increasingly intricate role of IL-17A and TH 17-associated cytokines in disease, informing our therapeutic decisions. Herein, we discuss important non-TH 17 cell sources of IL-17A and other TH 17-associated cytokines relevant to inflammatory events in mucosal tissues.